2021
DOI: 10.1016/j.radonc.2021.02.015
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-fibroblast activation protein inhibitor PET/CT on gross tumour volume delineation for radiotherapy planning of oesophageal cancer

Abstract: Background and purpose: To compare 68 Ga-fibroblast activation protein inhibitor (FAPI) and 18 F-FDG PET/ CT in imaging locally advanced oesophageal cancer, and evaluate the potential usefulness of 68 Ga-FAPI PET/CT on gross target volume (GTV) delineation aimed at radiotherapy planning for oesophageal cancer as compared with contrast-enhanced CT (CE-CT) and 18 F-FDG PET/CT. Materials and methods: Twenty-one patients with newly diagnosed oesophageal cancer who underwent both 18 F-FDG and 68 Ga-FAPI PET/CT scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 37 publications
0
53
0
Order By: Relevance
“…These findings were subsequently confirmed by Zhao et al in 21 patients with newly diagnosed esophageal cancer who underwent both 18 F-FDG and 68 Ga-FAPI-PET/CT scans. FAPI imaging showed favorable SUV metrics, TBRs and a superior target volume delineation [ 98 ].…”
Section: Malignant Conditionsmentioning
confidence: 99%
“…These findings were subsequently confirmed by Zhao et al in 21 patients with newly diagnosed esophageal cancer who underwent both 18 F-FDG and 68 Ga-FAPI-PET/CT scans. FAPI imaging showed favorable SUV metrics, TBRs and a superior target volume delineation [ 98 ].…”
Section: Malignant Conditionsmentioning
confidence: 99%
“…Regarding the normal tissue biodistribution of radiolabeled FAPI in comparison to [ 18 F]F-FDG, all the included studies showed a lower radiolabeled FAPI uptake in the normal brain, liver, and oral mucosa, compared to [ 18 F]F-FDG [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…No additional studies were found screening the references of the selected articles. Finally, 26 articles (925 patients) including data on the comparison between radiolabeled FAPI and [ 18 F]F-FDG as PET radiotracers in oncology were included in the systematic review [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. The characteristics of the studies selected for the systematic review are presented in Table 1 , Table 2 , Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 12/23 studies [ 68 Ga]Ga-FAPI was offered as a compassionate drug according to the German Medicinal Product Act § 13(2b) [25,26,35,36,[27][28][29][30][31][32][33][34]. In the remaining 10/23 papers, the trial phase was not speci ed or designated as "not applicable" [37][38][39][40][41][42][43][44][45][46]. In 18/23 studies [ 68 Ga]Ga-FAPI imaging was compared to other imaging technique(s).…”
Section: Systematic Reviewmentioning
confidence: 99%